MORPHOLOGICAL PROFILE BY VOLEYBALL SCHOOL ATHLETS IN PORTO VELHO CITY - RONDÔNIA (Fiep Bulletin - online, 2011)
The purpose of this study was to evaluate the morphological volleyball athletes, female, age between 12 and 14 years, at the student representatives of Porto Velho city student participants of the games of Rondônia, in 2004. The sample consisted of 20 athletes, with the following characteristics: age (13.40 ± 0.82 years), weight (51.75 ± 4.66 kg) and height (164.80 ± 5.63 cm). Was evaluated the body mass index (19.06 ± 1.48) and fat percentage (21.72 ± 3.31). It was concluded that the values corresponding to body mass index and fat percentage were presented in an excellent colocation of athletes within the normal range recommended for general populations.
Keywords: Volleyball; Body Mass Index; Percentage of fat